BUSINESS PROCESS OPTIMIZATION IN THE DIGITALIZATION ERA OF PRODUCTION - N. A. Popov (Real Economics Publishing House, 2019)
Various business process optimization methods associated with industrial companies are reviewed, e.g. the processes of production planning, equipment and inventory maintenance as well as quality control. Case studies of Russian and foreign companies are provided. The author can conclude that digital technologies provide a significant advantage when implemented in an industrial production environment to the demands of Industry 4.0 technologies. The most promising technologies are identified for implementation with a purpose to optimize industrial business processes. According to the findings of the study, implementing econometric methods, creating a cloud infrastructure and adopting digital devices using Internet of things concepts can be named among the most efficient measures for business process optimization in production companies.